Nodal Promotes Glioblastoma Cell Growth - de Silva, Tanya; Ye, Gang; Liang, Yao-Yun; Xu, Guoxiong; Peng, Chun (Frontiers in Endocrinology, 2012)
Nodal is a member of the transforming growth factor-ß (TGF-ß) superfamily that plays critical roles during embryogenesis. Recent studies in ovarian, breast, prostate and skin cancer cells suggest that Nodal also regulates cell proliferation, apoptosis, and invasion in cancer cells. However, it appears to exert both tumor-suppressing and tumor-promoting effects, depending on the cell type. To further understand the role of Nodal in tumorigenesis, we examined the effect of Nodal in glioblastoma cell growth and spheroid formation using U87 cell line. Treatment of U87 with recombinant Nodal significantly increased U87 cell growth. In U87 cells stably transfected with the plasmid encoding Nodal, Smad2 phosphorylation was strongly induced and cell growth was significantly enhanced. Overexpression of Nodal also resulted in tight spheroid formation. On the other hand, the cells stably transfected with Nodal siRNA formed loose spheroids. Nodal is known to signal through activin receptor-like kinase 4 (ALK4) and ALK7 and the Smad2/3 pathway. To determine which receptor and Smad mediate the growth promoting effect of Nodal, we transfected siRNAs targeting ALK4, ALK7, Smad2, or Smad3 into Nodal-overexpressing cells and observed that cell growth was significantly inhibited by ALK4, ALK7, and Smad3 siRNAs. Taken together, these findings suggest that Nodal may have tumor-promoting effects on glioblastoma cellsand and these effects are mediated by ALK4, ALK7, and Smad3.